Energy profiling via energy audit at FSKTM building towards energy efficiency in UTHM / Mohammad Fikrey Roslan and Mohamed Saiful Firdaus Hussin - Roslan, Mohammad Fikrey; Hussin, Mohamed Saiful Firdaus (2022)
This study aims to determine how much the Faculty of Computer Science and Information Technology (FSKTM) buildings in Universiti Tun Hussein Onn Malaysia (UTHM) utilized energy and to identify factors affecting the usage. An end-use energy analysis was conducted on the building to identify energy apportioning and energy end-use based on different categories such as air conditioning and mechanical ventilation (ACMV) system, lighting system, Information technology (IT) equipment, and other electrical equipment. The analysis was carried out by conducting desktop analysis and field data collection which also involved simple calculations. The Building Energy Index (BEI) was also calculated to measure the efficiency level of the building which was then compared to the Malaysian Standard, MS 1525. Upon completion, it is known that the largest energy consumption end-user in this faculty is the ACMV system which consumes approximately 43.0% of the total electrical energy. The BEI calculation revealed that the building has an index of 128.552 kWh/m2/year which is below than requirement set by Malaysian standard. To increase the building efficiency, energy conservation measures were proposed.